Komoditas Unggulan Tanaman Pangan Untuk Mendukung Perekonomian Wilayah Kabupaten Indramayu - Indri Mustikaningrum; Widjonarko Widjonarko (Ruang, 2018)
Regional development is a general effort to reduce regional disparities by supporting economic activities in regions. Regional development is also a strategy to utilize the internal and external factors to increase production of goods and services. Economic aspect can be used as an indicator to determine whether the regional development is success. Regional economic growth will be determined by the natural resources and demand for its poducts or commodities. Economic activity in developing-countries, depends on the agricultural sector. This sector has a great contribution to economic growth in most of regions. The economic growth of Kabupaten Indramayu depends on its agricultural activities as well, especially food crops agriculture. The food crops production of Kabupaten Indramayu is able to supply the national needs. Rice, corn, cassava, sweet potatoes, soybeans, peanuts and mung beans are the 7 commodities of food crops in Kabupaten Indramayu. Based on the research conducted by quantitative methods using Location Quotient analysis, Shift Share analysis and Domestic Resource Costs analysis, were found that rice and soybean are the region’s flagship commodities. Meanwhile, based on SWOT analysis, was found that improving the quality and quantity of irrigation infrastructures; improving the quality and quantity of human resources; applying modern agriculture methods; and paying attention to the land conversions, become the main strategies in developing flagship commodities of food crops.